2021
DOI: 10.3233/bmr-191771
|View full text |Cite
|
Sign up to set email alerts
|

Optimal activation ratio of the scapular muscles in closed kinetic chain shoulder exercises: A systematic review

Abstract: BACKGROUND: Muscle synergies contribute to scapular position during arm movement. The trapezius and serratus anterior (SA) muscles are the main stabilizers and are therefore the main target muscles of therapeutic exercises. OBJECTIVE: To systematically review the current literature investigating the optimal activation ratio of the scapular muscles during a range of closed kinetic chain exercises. METHODS: A systematic review search was conducted to identify studies reporting shoulder electromyography (EMG) act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The present investigation had limitations: (i) this report was based only on the EMG activity normalized by MVIC and did not consider the UT/SA ratio as a valid outcome measure for inter-subject comparisons. This measurement has been widely reported as the outcome that allows making comparisons between individuals and exercises, as well as this allows evaluating and analyzing the intra and inter-muscular balance ( Ludewig et al, 2004 ; Berckmans et al, 2021 ); (ii) as reported by other reviews ( Kang et al, 2019 ; Mendez-Rebolledo et al, 2021 ) most of the included studies did not present a priori a sample size or the statistical power of the analyzes, and they recruited participants healthy and asymptomatic, which make difficult to fully extrapolate the results of this research to populations with shoulder musculoskeletal dysfunctions; (iii) 93,3% the included studies showed a moderate methodological quality, mainly due internal validity aspects; and (iv) the present investigation was not able to carry out a meta-analysis for the push-up plus exercise, considering that add scapular protraction may increment the myoelectrical activity of the SA, involved directly in this movement. Finally, and according to GRADE, the certainty of evidence ranged from “very low” to “low” for the outcomes, harming the confidence in the presented estimates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present investigation had limitations: (i) this report was based only on the EMG activity normalized by MVIC and did not consider the UT/SA ratio as a valid outcome measure for inter-subject comparisons. This measurement has been widely reported as the outcome that allows making comparisons between individuals and exercises, as well as this allows evaluating and analyzing the intra and inter-muscular balance ( Ludewig et al, 2004 ; Berckmans et al, 2021 ); (ii) as reported by other reviews ( Kang et al, 2019 ; Mendez-Rebolledo et al, 2021 ) most of the included studies did not present a priori a sample size or the statistical power of the analyzes, and they recruited participants healthy and asymptomatic, which make difficult to fully extrapolate the results of this research to populations with shoulder musculoskeletal dysfunctions; (iii) 93,3% the included studies showed a moderate methodological quality, mainly due internal validity aspects; and (iv) the present investigation was not able to carry out a meta-analysis for the push-up plus exercise, considering that add scapular protraction may increment the myoelectrical activity of the SA, involved directly in this movement. Finally, and according to GRADE, the certainty of evidence ranged from “very low” to “low” for the outcomes, harming the confidence in the presented estimates.…”
Section: Discussionmentioning
confidence: 99%
“…An author (OC) completed the extraction of data from selected studies. Due to the heterogeneity of the nomenclature and design of the exercises reported in the literature, these were categorized according to previously described criteria ( Mendez-Rebolledo et al, 2021 ; Cappato de Araújo et al, 2021 ). A second author (MV) checked the accuracy and consistency of all entries and made relevant clarifications when necessary.…”
Section: Survey Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…There are previous reports on 4-point and 3-pod variations of the plank exercise (11,22,25,34). In previous studies, higher UT, MT, LT, SA, and IS muscle activation levels have been observed in the 3-pod plank and push-up variations compared with the 4-point exercises (11,21,25,32).…”
Section: Discussionmentioning
confidence: 99%
“…These, from now on free to read, 65 reviews provide us a meaningful insight in the current 66 evidence of MSD-related therapies. The first study, car-67 ried out by Mendez-Rebolledo and colleagues [1]…”
mentioning
confidence: 99%